PENGARUH PEMAHAMAN PENGELOLAAN KEUANGAN, SISTEM AKUNTANSI KEUANGAN DAERAH, TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN ENDE - Mbejo, Maria Apriliana Anita; Banda, Falentina Lucia; Thalib, Sabra B Wahab (Program Studi Akuntansi Universitas Flores, 2023)
The aim of this research is to determine the effect of understanding the financial management of the regional financial accounting system on the performance of the Ende Regency Regional Government. The population in this study was the Head of Section, Secretary and Treasurer for Finance, totaling 159. The sampling technique used purposive sampling, namely the Head of Section, Secretary and Treasurer for Finance in SKPD Ende Regency, totaling 60 people. This type of research uses the type of causality research. This study uses primary data, namely a questionnaire. Data were analyzed using multiple regression analysis which was processed through 1MB SPSS Statistikcever 25. The results of this study indicate that: (1) Understanding of financial management has a significant positive effect on the performance of the local government of Ende Regency. This can be shown by the coefficient value of the variable understanding of financial management of 0.202 with tcount > ttable (4.808> 2.202) and a significant level of understanding of financial management is 0.000 <0.05. (2) The regional financial accounting system has a significant positive effect on the performance of the local government of Ende Regency. This can be shown by the variable coefficient of the regional financial accounting system of 2.239 with tcount > ttable (2.239> 2.002) and the significant level of the regional financial accounting system is 0.029 <0.05. Simultaneously, the variable understanding of financial management and regional financial accounting systems on local government performance is 29.4 while the remaining 70.6% is influenced by other variables not included in the study.